2016
DOI: 10.1371/journal.pone.0149443
|View full text |Cite
|
Sign up to set email alerts
|

Stress Exposure in Significant Relationships Is Associated with Lymph Node Status in Breast Cancer

Abstract: ObjectiveLife stress exposure may impact on health and disease. Previous literature showed that stressful life events are associated with cancer incidence, survival and mortality. In animal models, patterns of maternal care have been shown to critically affect stress sensitivity and immunity trajectories later in life, by modifying DNA methylation during critical periods early in life. However, the role of parental care in breast cancer progression and survival has only limitedly been explored. Here, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 39 publications
1
11
0
1
Order By: Relevance
“…[130][131][132] When a potentially risky event is perceived by the subject as overwhelming the available resources (such as coping strategies and social support), the nervous system activates pathways that release catecholamines, corticosteroids, and opioids. 133 Because the receptors for these chemical signals (neurotransmitters, neuropeptides, neurohormones, and adrenal hormones) are also located on lymphocytes and macrophages, the release of these cerebral messengers can influence immune and endocrine functionality (see Figure 3) in vivo and in vitro. 134 Through these mechanisms the brain exerts an immunoregulatory role in oncologic diseases.…”
Section: Relevance Of Neuropsychopathological Abnormalities For the Cmentioning
confidence: 99%
See 1 more Smart Citation
“…[130][131][132] When a potentially risky event is perceived by the subject as overwhelming the available resources (such as coping strategies and social support), the nervous system activates pathways that release catecholamines, corticosteroids, and opioids. 133 Because the receptors for these chemical signals (neurotransmitters, neuropeptides, neurohormones, and adrenal hormones) are also located on lymphocytes and macrophages, the release of these cerebral messengers can influence immune and endocrine functionality (see Figure 3) in vivo and in vitro. 134 Through these mechanisms the brain exerts an immunoregulatory role in oncologic diseases.…”
Section: Relevance Of Neuropsychopathological Abnormalities For the Cmentioning
confidence: 99%
“…Depressive symptoms and psychosocial stressors can be considered risk factors for cancer incidence and mortality by affecting several neuroimmunological and neuroendocrinological biochemical pathways 130 132 When a potentially risky event is perceived by the subject as overwhelming the available resources (such as coping strategies and social support), the nervous system activates pathways that release catecholamines, corticosteroids, and opioids 133 . Because the receptors for these chemical signals (neurotransmitters, neuropeptides, neurohormones, and adrenal hormones) are also located on lymphocytes and macrophages, the release of these cerebral messengers can influence immune and endocrine functionality (see Figure 3) in vivo and in vitro.…”
Section: Relevance Of Neuropsychopathological Abnormalities For the Cmentioning
confidence: 99%
“…Various studies linked chronic stress, exposure to stressful events, and inflammation markers among breast cancer (BC) patients [ 26 , 27 , 28 , 29 , 30 ]. For example, a longitudinal pilot study found that participants with BC (n = 20) exposed to childhood trauma had significant depressive symptomatology and fatigue levels.…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal study revealed that a lack of social support (a form of social isolation) predicted higher IL-6 levels and depressive symptoms among BC survivors [ 29 ]. Furthermore, early relational stress exposure (represented by non-optimal parental bonding, such as rejection and neglect) was significantly associated with a positive lymph node status in a group of BC patients scheduled for surgery [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 A secreção crônica de cortisol, em resposta a eventos estressores, tem sido associada com o desenvolvimento de patologias diversas como: doença cardíaca coronoriana, 4 osteoporose, 8 úlcera de membros inferiores 9 e recentemente há um crescente número de estudos que apontam uma correlação positiva entre aumentos crônicos dos níveis plasmáticos de cortisol induzido por estresse e desenvolvimento de neoplasias. [10][11][12][13] Tentativas de associar a etiologia das neoplasias malignas com os eventos estressantes diários datam desde a Grécia antiga, onde Galeno sugeria que mulheres melancólicas e depressivas eram mais propensas a desenvolver o câncer do que aquelas com um alto astral. 6 Embora até então muitos estudos tenham sido realizados neste âmbito, ainda não há um consenso quanto à influência dos eventos estressores diários no desenvolvimento de neoplasias.…”
Section: Introductionunclassified